Chief editor notation / Irina Mohd Akhir - Mohd Akhir, Irina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
The Centre of Hotel & Tourism Management Studies is pleased to announced, that 2018 was indeed a hectic year due to numerous programmes and publications were being conducted. Subsequently, with all the hard work leading into the publishing of Hot & Tour Newsletter issue 1, 2019. The first Hot & Tour Newsletter was published in 2017; and the previous editorial board was extremely pleased with the overwhelming support from the authors as well as the readers. Moreover, many interesting and exciting articles will be featuring in the current issue and in the 2nd issue by the end of the year. In the meantime, the publication unit are planning to publish two issues yearly in full colours; besides allowing more authors to contribute their articles and fulfilling the general publication requirements. Evidently, the improvement in publication such as getting copyright permission of pictures used in articles, authorization agreements of covered stories and designing new templates are among others that have been planned in the following issue. In this newsletter, I wish all the writers and readers a very successful